Osteopenia/Osteoporosis and Its Association with Sarcopenia: EpiFloripa Aging Study 2013/2014 - Susana Cararo Confortin; Lariane Mortean Ono; Larissa Pruner Marques; Gilciane Ceolin; Eleonora d'Orsi; Aline Rodrigues Barbosa (Karger Publishers, 2020)
Objective: To verify the association between sarcopenia and osteopenia/osteoporosis in the older population from Florianópolis, Southern Brazil. Methods: A cross-sectional study with 598 older adults. The bone mineral density (BMD) was evaluated by total BMD, lumbar spine BMD (LS-BMD), femoral neck BMD (FN-BMD), and osteopenia/osteoporosis was defined when BMD (g/cm2) <-1 standard deviation of the sample mean. Sarcopenia was identified by the appendicular muscle mass index (AMMI), by sex, when AMMI <7.26 kg/m2 for men and <5.5 kg/m2 for women. Results: Of the 598 subjects (63-93 years) in the sample, 65.4% were women. The proportion of altered BMD was 52.1% for total BMD, 62.5% for LS-BMD, and 70.9% for FN-BMD in women, while for men, altered BMD proportion was 29.3% for total BMD, 24.5% for LS-BMD, and 64.9% for FN-BMD. After adjustments, sarcopenia was associated with increased odds of altered LS-BMD (OR: 12.25; 95% CI: 3.66-40.96 and OR: 2.90; 95% CI: 1.30-6.48) and FN-BMD (OR: 5.59; 95% CI: 1.64-19.05 and OR: 7.95; 95% CI: 3.23-19.57), respectively for women and men. The association between sarcopenia and altered total BMD (OR: 11.08; 95% CI: 3.84-31.97) was observed only in women. Conclusion: The proportion of osteopenia/osteoporosis was higher in women. Sarcopenia was associated with osteopenia/osteoporosis in the population from Florianópolis, except for total BMD in men.